Modeling of debris flow depositional patterns according to the catchment and sediment source area characteristics - Tiranti, Davide; Deangeli, Chiara (Frontiers in Earth Science, 2015)
A method to predict the most probable flow rheology in Alpine debris flows is presented. The methods classifies outcropping rock masses in catchments on the basis of the type of resulting unconsolidated deposits. The grain size distribution of the debris material and the depositional style of past debris flow events are related to the dominant flow processes: viscoplastic and frictional/collisional. Three catchments in the upper Susa Valley (Western Alps), characterized by different lithologies, were selected for numerical analysis carried out with a Cellular Automata code with viscoplastic and frictional/collisional rheologies. The obtained numerical results are in good agreement with in site evidences in terms of depositional patterns, confirming the possibility of choosing the rheology of the debris flow based on the source material within the catchment.